2021
DOI: 10.3390/su13073820
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Emergency Remote Education in COVID-19 Crisis Focused on the Perception of the Teachers

Abstract: This descriptive study intends to identify the satisfaction perception among the teachers of the Universidad del Valle de México (UVM) concerning the use of the Microsoft Teams platform in the transition from traditional model (face-to-face) to 100% online education [Emergency Remote Teaching (ERT)]. The proposal aims to determine the perspectives of teachers regarding the use of the Microsoft Teams platform during the crisis caused by COVID-19. UVM has 6938 full-time teachers and part-time teachers who collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…Halim et al [30]; Jamaludin et al [6]; Ishak and Mansor [43]; Alakrash and Razak [37]; Miranda et al [20]; Zamora-Antuñano, [50];…”
Section: Contributions By Countrymentioning
confidence: 99%
See 1 more Smart Citation
“…Halim et al [30]; Jamaludin et al [6]; Ishak and Mansor [43]; Alakrash and Razak [37]; Miranda et al [20]; Zamora-Antuñano, [50];…”
Section: Contributions By Countrymentioning
confidence: 99%
“…This barrier is prevalent in developing economies due to insufficient infrastructures and other resources that facilitate the training of professionals (B5) on digital technologies essential to the implementation of EDUC4 [20,37,50]. It is more relevant in developing countries having relatively lower computer literacy [54].…”
Section: Human Resourcesmentioning
confidence: 99%
“…During the period of the pandemic, a variety of software products have been used in the remote learning process, including Zoom, Skype, WhatsApp, Blackboard Collaborate, among others, and radio and television as well [44][45][46][47]. A study conducted at Universidad del Valle de México confirmed teachers' ability to assimilate quickly in the Ms Teams environment [48]. Satisfaction with a range of digital communication tools used for elearning was demonstrated in a study conducted among students in St. Petersburg in 2020 [49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surveys on consumers' perspectives are essential for figuring out what should be done to optimize an online system further. From the perspective of education, there are surveys on the satisfaction perception among the teachers of a university in the utilization of an online service [ 18 ]. Some surveys and analyses look into the perception of satisfaction among students in using an online-based educational service [ 19 ].…”
Section: Introductionmentioning
confidence: 99%